1957
DOI: 10.1111/j.1476-5381.1957.tb00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin, Ouabain and Potassium Movements in Rabbit Auricles

Abstract: Movements of potassium have been observed in isolated right and left auricles of rabbits by means of radioactive tracer. The tissues have been immersed in a modified Krebs saline at 370, and in these conditions showed only small changes in ionic content over periods up to 6 hr.The extracellular volume, determined with inulin and with 2"Na, was large (44.1 ml./100 g. tissue), and accounted for about 3.8% of the tissue potassium. Left auricles exchanged without gross inhomogeneity: the rate of exchange was about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

1959
1959
1966
1966

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 17 publications
(4 reference statements)
3
38
0
Order By: Relevance
“…Rabbit auricles were used because much is known about their normal potassium exchanges and the effects of drugs upon them (Rayner & Weatherall, 1957, 1959Persoff, 1960;Waddell, 1961;Weatherall, 1962). Small rabbits (<1.5 kg) were killed by a blow on the head and the heart removed rapidly.…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit auricles were used because much is known about their normal potassium exchanges and the effects of drugs upon them (Rayner & Weatherall, 1957, 1959Persoff, 1960;Waddell, 1961;Weatherall, 1962). Small rabbits (<1.5 kg) were killed by a blow on the head and the heart removed rapidly.…”
Section: Methodsmentioning
confidence: 99%
“…The fast part is not due to the anatomical pacemaker, as we previously suggested (Rayner & Weatherall, 1957), because a similar fraction appears in left auricles when they are driven electrically. Earlier experiments (Rayner & Weatherall, 1957 , Table 3) suggested that there was no fast uptake by left auricles which were beating in undivided pairs, but the results could have been vitiated by inadequate allowance for the effects of cutting the bridge of tissue between the two auricles.…”
Section: Discussionmentioning
confidence: 61%
“…The fast part is not due to the anatomical pacemaker, as we previously suggested (Rayner & Weatherall, 1957), because a similar fraction appears in left auricles when they are driven electrically. Earlier experiments (Rayner & Weatherall, 1957 , Table 3) suggested that there was no fast uptake by left auricles which were beating in undivided pairs, but the results could have been vitiated by inadequate allowance for the effects of cutting the bridge of tissue between the two auricles. If it is assumed that exchange of a little potassium (2-4 %) of each auricle is accelerated by such a cut (as it may be by end effects and increased surface area) the typical difference between active and inactive tissue is apparent and the previously unexplained discrepancy in the faster uptake of separated than undivided right auricles is accounted for.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations